Analysis of Oxidative Stress-Related Markers in Crohn's Disease Patients at Surgery and Correlations with Clinical Findings - Cristina Luceri; Elisabetta Bigagli; Sara Agostiniani; Francesco Giudici; Daniela Zambonin; Stefano Scaringi; Ferdinando Ficari; Maura Lodovici; Cecilia Malentacchi (MDPI AG, 2019)
Crohn’ disease (CD) patients are at high risk of postoperative recurrence and new tools for the assessment of disease activity are needed to prevent long-term complications. In these patients, the over-production of ROS generated by inflamed bowel tissue and inflammatory cells activates a pathogenic cascade that further exacerbates inflammation and leads to increased oxidative damage to DNA, proteins, and lipids. We measured the products of protein/lipid oxidation and the total antioxidant capacity (ferric reducing ability of plasma, FRAP) in the serum of CD patients with severe disease activity requiring surgery with the aim to characterize their redox status and identify associations between oxidative stress-related markers and their clinical characteristics. At the systemic level, CD was associated with increased levels of protein and lipid oxidation products when compared to healthy volunteers, even though the FRAP values were similar. Advanced oxidation protein product (AOPP) levels showed the highest difference between patients and the controls (11.25, 5.02−15.15, vs. 1.36, 0.75−2.70, median, interquartile range; p < 0.0001) and the analysis of receiver operating characteristic (ROC) curves, indicated for AOPP, the best area under the curve (AUC) value for CD prediction. Advanced glycated end-products (AGEs) were also significantly higher in CD patients (p < 0.01), which is of interest since AOPP and AGEs are both able to activate the membrane receptor for advanced glycation end products (RAGE) involved in inflammatory diseases. Thiobarbituric acid reactive substance (TBARS) levels were significantly higher in CD patients with ileal localization and aggressive disease behavior, in smokers, and in patients suffering from allergies. In conclusion, our data indicate that circulating oxidative stress biomarkers may be attractive candidates as disease predictors as well as for clinical or therapeutic monitoring of CD. Our results also suggest that AOPP/AGEs and RAGE signaling may represent a pathogenic factor and a potential therapeutic target in CD.